Drip-Applied Noni Waste Fertilizer for Improved Allium fistulosum Yield - Radiatul Ummah; Reni Ekawaty (Agricultural Revolution Journal, 2025)
Spring onion (Allium fistulosum), a commonly grown and economically significant vegetable utilized in various culinary applications, served as the test crop in this self-funded entrepreneurial endeavor. The discarded remnants of the noni fruit present a promising avenue for creating liquid organic plant food through a two-week microbial digestion. As a precise and water-prudent irrigation strategy, drip technology allows for the targeted delivery of moisture directly to the root systems of plants via a network of porous plastic conduits or dispensing devices. The objectives of this research were to generate liquid organic fertilizer from noni fruit waste, determine its levels of essential macronutrients—Nitrogen (N), Phosphorus (P), and Potassium (K), which were quantified at 0.11%, 0.05%, and 0.10% respectively—assess the operational effectiveness of a drip irrigation setup, and contrast the developmental patterns of spring onions nourished with a standard AB Mix nutrient solution (group A) against those receiving the liquid organic fertilizer derived from noni fruit waste. The execution of this study encompassed several stages: procurement of necessary equipment and supplies, assembly of the drip irrigation system, two evaluations of the irrigation system's functionality, production of the nutrient solution from noni waste, preparation of the growth substrate, seedling acclimatization and relocation, nutrient application, monitoring of growth indicators, and the final harvest.  The outcomes of this research support the inference that discarded noni fruit can be successfully converted into a liquid organic plant nutrient solution through a two-week fermentation process facilitated by EM4 activation.